Design of multiprobe devices for electronic components with ball leads testing - Nevlyudov, I. Sh.; Palagin, V. A.; Razumov-Frizyuk, E. A.; Zharikova, I. V. (Technology and design in electronic equipment, 2016)
In the article, design and technological features of multiprobe connecting device for testing the electronic components with matrix ball leads are described and substantiated. Such test fixture has probes made as two separated flatcontact lands that can be used for testing BGA/CSP components or microelectromechanical devices. Only in case, when two parts of probe contact lands are pressed to according lead of electronic component, electrical circuit between them closes. This fact confirms presence of contact between testing fixture probe and tested lead of BGA device and can be considered as way of testing reliability increasing. Due to the proposed new form of contact probe for electronic component testing, it became possible to simplify the topology of connecting circuit board.Developed commutative board with ZIF connectors allows realizing multiprobe device connection to automated measuring systems, providing also the possibility of its future application to test other electronic components with more leads. Also, the results of experimental and modeling research of developed device prototype are presented and explained. Obtained results substantiate the basic requirements for the multiprobe connecting device that should be observed during its contacting to the unit under test.Designed test fixture is more simple and cheap in comparison with its analogues. Also, the developed method of testing effectively provides the necessary contact pressure between test fixture and unit under test without hazard of its deformation, which can appear in similar devices.